2019
DOI: 10.4041/kjod.2019.49.3.140
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the accuracy and efficiency of dental movements with Invisalign®

Abstract: We are currently living in an era where the use of computer-aided design/computer-aided manufacturing has allowed individualized orthodontic treatments, but has also incorporated enhanced digitalized technology that does not permit improvisation. The purpose of this systematic review was to analyze publications that assessed the accuracy and efficiency of the Invisalign® system. A systematic review was performed using a search strategy to identify articles that referenced Invisalign®, which were published betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(121 citation statements)
references
References 32 publications
3
110
0
8
Order By: Relevance
“…Recent studies have shown that patients specifically treated with Invisalign were satisfied with their esthetic results and showed an improvement in their QoL, especially when related to their smile and during chewing and eating functions analyzed after treatment [13,27]. However, concerning the efficacy of treatment, recent systematic reviews have suggested that this treatment modality presents some difficulties on specific orthodontic movements when compared with fixed appliances such as in rotation and vertical movements [14], ideal occlusal contacts, torque control, increasing transverse width and retention [16]. In addition, a study that evaluated the results of treatments performed with Invisalign and conventional brackets according to the American Board of Orthodontics' objective classification system showed that treatment with fixed appliances are relatively superior than the treatment performed with Invisalign [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that patients specifically treated with Invisalign were satisfied with their esthetic results and showed an improvement in their QoL, especially when related to their smile and during chewing and eating functions analyzed after treatment [13,27]. However, concerning the efficacy of treatment, recent systematic reviews have suggested that this treatment modality presents some difficulties on specific orthodontic movements when compared with fixed appliances such as in rotation and vertical movements [14], ideal occlusal contacts, torque control, increasing transverse width and retention [16]. In addition, a study that evaluated the results of treatments performed with Invisalign and conventional brackets according to the American Board of Orthodontics' objective classification system showed that treatment with fixed appliances are relatively superior than the treatment performed with Invisalign [28].…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews have evaluated the efficiency of orthodontic treatment with clear aligners and they suggested that the outcomes are not as accurate as those with fixed appliances [14][15][16]. On the other hand, treatment done with clear aligners present some advantages such as overall decreased treatment and chair time in patients with mild to moderate malocclusions [17].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Invisalign gained popularity as one of the most esthetic options for tooth movement and is now one of the most widely used aligner systems. 5 Today, a significant portion of the world's population has access to numerous websites and social media platforms that provide health care information. In recent surveys, 80% of Internet users reported accessing online health information.…”
Section: Introductionmentioning
confidence: 99%
“…Nachteil im Vergleich zu festsitzenden Klasse-II-Apparaturen ist das schwierigere Einstellen einer stabilen, gut abgestützten Okklusion. Als Nebenwirkung durch die Gummizüge kann es zu einer Rotation der Okklusionsebene im Uhrzeigersinn kommen [12].…”
Section: Fallbeispielunclassified